Production of sheep grazing on nitrogen-fertilized tifton 85 grass in continuous stocking - Andréia Luciane Moreira; Jailson Lara Fagundes; Eidi Yoshihara; Alfredo Acosta Backes; Leandro Teixeira Barbosa; Reges Heinrichs (Acta Scientiarum. Animal Sciences, 2014)
Biomass and forage volume density and the performance and stocking rate of sheep on pastures with nitrogen-fertilized Tifton 85 and subjected to a continuous stocking system were evaluated. Four doses of nitrogen (0, 100, 200, and 400 kg ha-1 year), arranged in an experimental design with randomized blocks and four replications, were analyzed. Sixteen paddocks and Santa Inês sheep were used as test animals, coupled to crossbreed Santa Inês sheep as regulating animal stocking. Nitrogen-fertilized Tifton 85 pastures increased the amount of forage biomass and volume density which affected stocking rate and weight gain of sheep in continuous grazing. When pastures with Tifton 85 were administered in variable load continuous stocking, with grass kept at 15 cm, nitrogen fertilization up to 400 kg ha-1 year is recommended.